Clinical outcomes of nephroureterectomy with bladder cuff excision or radical cystectomy for distal ureteral carcinoma invaded muscle of the ureteral orifice - Pan Li; Suoshi Jing; Yindong Kang; Bin Feng; Yunxin Zhang; Hui Ding; Juan Wang; Yingru Wang; Li Yang; Zhilong Dong; Junqiang Tian; Zhiping Wang; et al. (BMC Cancer)
Abstract Purpose To present the clinical outcomes of nephroureterectomy with bladder cuff excision (NU-BCE) or radical cystectomy (NU-RC) when distal ureteral carcinoma invaded muscle of the ureteral orifice using inverse probability of treatment weighting (IPTW). Methods This multicenter study retrospectively studied the demographics and perioperative outcomes of 59 patients who underwent NU-BCE or NU-RC between 2003 and 2024. Relapse-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS) were presented using Kaplan–Meier curves. Cox proportional hazard regression to find independent predictors. Results Of all patients, the median follow-up time for RFS was 8 months and 18 months for CSS and OS. After IPTW, the median RFS, CSS, and OS for patients who underwent NU-BCE and NU-RC was 9 vs. 27 months (p = 0.037), 18 vs. 40 months (p = 0.027), 18 vs. 30 months (p = 0.371), respectively. The mortality due to progression and complications in NU-BCE and NU-RC patients were 56.4% vs. 20.4% and 2.2% vs. 22.9% (p = 0.016). NU-BCE reduced the median operation time, blood loss, and drainage volume. Apart from NU-RC (HR, 0.18; 95%CI: 0.08–0.44; p < 0.001) (HR, 0.28; 95%CI: 0.1–0.79; p = 0.016) and tumor volume(HR, 1.17; 95%CI: 1.06–1.29; p = 0.002) (HR, 1.21; 95%CI: 1.11–1.31; p < 0.001), which are independent prognostic factors for RFS and CSS, another independent prognostic factor for CSS is the ureteral carcinoma with renal pelvic carcinoma (HR, 4.32; 95%CI: 1.28–14.511; p = 0.018). Conclusions Patients who underwent NU-RC had better RFS and CSS than NU-BCE, but there was little difference in OS due to the higher mortality rate of postoperative complications in the NU-RC.